2014
DOI: 10.1073/pnas.1407716111
|View full text |Cite
|
Sign up to set email alerts
|

Spin-dependent electron transport in protein-like single-helical molecules

Abstract: We report on a theoretical study of spin-dependent electron transport through single-helical molecules connected by two nonmagnetic electrodes, and explain the experiment of significant spin-selective phenomenon observed in α-helical protein and the contradictory results between the protein and single-stranded DNA. Our results reveal that the α-helical protein is an efficient spin filter and the spin polarization is robust against the disorder. These results are in excellent agreement with recent experiments [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
249
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(265 citation statements)
references
References 38 publications
7
249
0
Order By: Relevance
“…This description of the helical molecule is similar to that investigated in previous works 38,39,44,45 in a two-terminal geometry, where TRS or unitraity is effectively broken, as discussed in Sec. I.…”
Section: Three-terminal Helical Moleculesupporting
confidence: 66%
“…This description of the helical molecule is similar to that investigated in previous works 38,39,44,45 in a two-terminal geometry, where TRS or unitraity is effectively broken, as discussed in Sec. I.…”
Section: Three-terminal Helical Moleculesupporting
confidence: 66%
“…A number of theoretical models have been put forward to explain the observed spin selectivity in helical molecules. Usually they rely on large SOC [4][5][6][7][8][9][10][11][12], the need for dephasing when SOC is weak [13,14], the leakage of electrons from the molecule to the environment [15], the role of the bonding of the molecule to the metallic leads that enhance the effect [16,17], or the interplay between a helicity-induced SOC and a strong dipole electric field, which is characteristic of these molecules [18] (see [19,20] for a recent review). Theoretical models usually assume rigid lattices and neglect the local deformation of the molecule about the carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Our calculations are performed for the range 0.01 ∼ 0.6 of α values, which are about four orders of magnitude larger. It is customary 13,14 to adopt such values for the analysis of the effect of the chiral-induced spin selectivity. 43 Figure 7 (b) exhibits the energy dependence of the spin-resolved conductance for N mol = 23 when an unpolarized electron is injected.…”
Section: Landauer-type Formulamentioning
confidence: 99%
“…8,10 Since such organic molecules do not contain magnetic atoms, it has been suggested that the only possible origin of the CISS effect would be the SOI. In recent theoretical studies, the underlying physical mechanism of the spin polarization are studied for a double-stranded DNA 12 and for single-stranded molecules, 13,14 using the tight-binding model with Rashba-like SOI. Moreover, a minimal realistic model accounting for the nature of porbitals are shown to exhibit possible CISS effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation